2022
DOI: 10.3390/nu14204223
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Alcohol Spectrum Disorder and Iron Homeostasis

Abstract: Prenatal alcohol exposure results in a spectrum of behavioral, cognitive, and morphological abnormalities collectively referred to as fetal alcohol spectrum disorder (FASD). FASD presents with significant phenotypic variability and may be modified by gestational variables such as maternal nutritional status. Iron serves a critical function in the development of and processes within central nervous system (CNS) structures. Gestational iron deficiency alters CNS development and may contribute to neurodevelopment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…Clinical studies have revealed that there are change in iron metabolism in substance use disorders including alcohol abuser. 28 31 , 52 , 53 A study conducted in chronic cocaine user revealed that iron content was significantly higher in basal ganglia reward regions than that of control individuals. 54 It was also reported that iron mediates morphine -induced ferritin heavy chain upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have revealed that there are change in iron metabolism in substance use disorders including alcohol abuser. 28 31 , 52 , 53 A study conducted in chronic cocaine user revealed that iron content was significantly higher in basal ganglia reward regions than that of control individuals. 54 It was also reported that iron mediates morphine -induced ferritin heavy chain upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal consumption of alcoholic drinks during pregnancy has a significant impact on children’s neurodevelopment, intellectual capacity, and learning ability [ 97 , 98 ]. Often, this consumption can lead to the development of Fetal Alcohol Spectrum Disorder (FASD), which is characterized by dysmorphic facial features, fetal growth restriction, and restricted brain growth, resulting in neurobehavioral impairment throughout life [ 97 , 98 , 99 , 100 ]. Although they share similarities, FASD and ASD are distinct entities.…”
Section: The Influence Of Environmental Hazardsmentioning
confidence: 99%
“…When iron storage becomes overloaded, excess Fe 2+ is transported to the labile iron pool (LIP) via divalent metal transporter 1. 34 Bidirectional regulation of iron metabolism is facilitated by cellular proteins. Conversely, Fe 3+ enters cells through the transferrin (TF)/transferrin receptor 1 (TFR-1) transport system, and upregulation of iron-related proteins can also cause intracellular iron overload.…”
Section: Abnormal Iron Metabolism In the Brainmentioning
confidence: 99%